Answer:
n-315=1245
Step-by-step explanation:
n stands for the original amount of the loan. Margo has paid $315, so the original number minus what Margo has paid, and the equality is the amount that Margo still owes.
Answer:
so thank you for points
Step-by-step explanation:
3) 6.35
<span>The correct answer is:
[B]: "
m = -12 " .
________________________________________________________Explanation:_________________________________________________________Given the equation:</span>
→ <span>"
³√(m − 4) − ³√(2m + 8) = 0 " ; Solve for "
m" ;
_________________________________________________________We start by rewriting the terms in the equation:
_________________________________________________________Note the following property of exponents:_________________________________________________________ </span>→
"
a ⁽ ˣ / ʸ⁾ = ʸ√(aˣ) ; { y 0 } " ;
_________________________________________________________
So, rewrite: "
³√(m − 4) " ; as: "
(m − 4) ⁽ ¹/³⁾ " ;
and rewrite: "
³√(2m + 8) " ; as: "
(2m + 8) ⁽ ¹/³⁾ " ;
_________________________________________________________ And rewrite the question as:
_________________________________________________________
→ "
(m − 4) ⁽ ¹/³⁾ − (2m + 8) ⁽ ¹/³⁾ = 0 " ; Solve for "
m" ;
<span>
_________________________________________________________</span>Add "
(2m + 8) ¹/³ " to EACH SIDE of the equation; as follows:
_________________________________________________________ → (m − 4) ¹/³⁾ − (2m + 8)¹/³ + (2m + 8) ¹/³ = 0 + (2m + 8) ¹/³ ;
to get:
_________________________________________________________ → "
(m − 4) ¹/³ = (2m + 8) ¹/³ " ;
_________________________________________________________ → {
<u>Note</u>: If "
x ⁿ
= y ⁿ ;
then "
x = y " .
} .
_________________________________________________________ As such:
→
"
m − 4 = 2m + 8 " ;
Solve for "
m"
;
_________________________________________________________
Subtract "
2m" from each side of the equation; & add "
4" to each side of the equation; as follows:
_________________________________________________________
m − 4 − 2m + 4 = 2m + 8 − 2m + 4 ;
to get:
_________________________________________________________
→ -1m = 12 ;
Now, divide each side of the equation by "
-1 " ;
to isolation "
m" on one side of the equation; & to solve for "
m" ;
→
-1m / -1 = 12 / -1 ;
_________________________________________________________
to get:
_________________________________________________________"
m = -12 " ;
→ which is:
Answer choice: [B]: "
m = -12 " .
_________________________________________________________Hope this helps!
Best wishes.
_________________________________________________________
Answer:
7^2
3^3
Step-by-step explanation:
Exponents signify how many times the base is multiples by itself. In the case of 7x7, 7 is the base and it is being multiplied by twice itself, resulting in an answer of 7^2